Application of Ash for Amelioration of Salinity Effect in Rice (Bangladesh Agronomy Journal, 2017)
Agricultural land use in coastal area covers 53% and the lands are mostly affected by salinity. Besides, the average yield of rice in these areas is very low due to salinity. Although, BRRI has developed salt registrant rice varieties, the average production can be improved through soil management. Thus, a pot experiment was conducted in the net house of Department of Agronomy, Bangladesh Agricultural University, Mymensingh, during March to August 2010 to investigate the ameliorative effect of ash application on yield and yield attributes of rice under various salinity levels. Rice var. BRRI dhan47 (a salt tolerant variety) was used in the experiment. The sodium chloride induced salinity levels were 20, 40, 60, 80 and 100 mM NaCl and the levels of ash applied were 1.5, 3, 4.5 and 6 t ha-1. Results revealed that the different levels of salinity had significant adverse effect on plant height, tillers hill-1, panicle hill-1, grains panicle-1, 1000-grain weight, grain yield, biological yield and harvest index. All the plants eventually died when they were exposed to salinity level of 40 mM NaCl or more and could not survive up to maturity. Application of ash enhanced the yield attributes and yield of rice under different salinity levels compared to those without ash. It was concluded that application of ash at the rate of 6 t ha-1 ameliorated the salinity stress effect on rice yield of BRRI dhan47.Bangladesh Agron. J. 2017, 20(1): 31-36